Resultados de um programa de terapia sonora e orientação audiológica para zumbido - Freitas, Thaís Mendonça Maia Wanderley Cruz de (2020)
ABSTRACT – ARTICLE 1 - INTRODUCTION: Tinnitus, a sound perceived in the absence of an external sound source, is a symptom that has become common in the world population. Its multiple cause, subjective evaluations and consequently varied therapeutic possibilities have hampered its treatment success. Research has shown effectiveness for sound therapy accompanied by guidance. AIM: In view of this problem, the present research aimed to evaluate the profile of scientific productions in Hearing Aid with Individual Sound Generator and guidance. As well as, compare the results of the applicability of a protocol of sound therapy and audiological guidance for tinnitus and hearing loss. METHOD: For this purpose, two articles were developed. The first consists of a bibliometric analysis of the literature, which sought studies published without restriction of year and was carried out in the databases Pubmed / Medline, Lilacs, Web of science and Cochrane, using the descriptors (counseling) AND (tinnitus) as a search strategy. ) AND (hearing aids). The other article addressed a non-randomized (quasi-experimental), analytical (cause and effect), longitudinal clinical trial that verified the applicability of a sound therapy protocol and audiological guidance for tinnitus and hearing loss. RESULTS: In the review, 169 articles were identified and, of these, 37 met the eligibility criteria and 17 studies were selected to perform the bibliometric analysis. In the clinical trial, the tinnitus handicap questionnaire (Total score), decreased throughout the assessment until the fourth reassessment, and also on the emotional and catastrophic scales. There was an increase in the use of the individual hearing aid from the first reassessment to the fourth. And the total score of the tinnitus questionnaire was significant when comparing the groups in the fourth reassessment. CONCLUSION: The current review on the theme has shown that studies are becoming more and more frequent, involving researchers from several countries, but there are still gaps. And the results of sound therapy with guidance show that the suggested protocol is promising. It is suggested the applicability in a larger group.